ANALISIS HUKUM ISLAM TERHADAP PENGELOLAAN HOTEL SYARIAH DI TASIKMALAYA (Studi Kasus di Hotel Srikandi Kota Tasikmalaya) - Vissa Reiensefa T Wanita; Zainul Abidin, Muhamad; Abidin, Zainul (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2024)
Sharia hotels in the hospitality industry have become a trend in the accommodation business in some areas of Indonesia. This phenomenon is also an indicator that the presence of hotels in Indonesia is very worrying, a lot of hotels that do not apply the principle of Shariah. The Shariah hotel is now the modern necessity of the Muslim community. Not a few of the hotels are often used as a rule-free place. But srikandi hotels have their own rules as standardization of sharia hotels. The method used in this research is qualitative using field research methods for data collection using observations, interviews and documentation. The main source in this research is the manager and staff of Hotel Srikandi Kota Tasikmalaya. The results of this study show that according to Q.s An- Nahl paragraph 89 hotel srikandi has applied the principles of Shariah. Besides, based on Q.S At-Talaq paragraph 6 hotel srekandi has fulfilled all the rations and conditions in the academic rental-renting (ijarah). Although the hotel srikandi has not applied the principle of full Shariah, the rental is still valid, so the renting of the hotel rooms is valid according to Islamic law.